Reduced Socioeconomic Disparities in Cleft Care After Implementing a Cleft Nurse Navigator Program. (March 2022) - Wagner, Connor; Zimmerman, Carrie E.; Barrero, Carlos; Kalmar, Christopher L.; Butler, Paris; Guevara, James; Bartlett, Scott P.; Taylor, Jesse A.; Folsom, Nancy; Swanson, Jordan W.
Objective: To evaluate the impact of a Cleft Nurse Navigator (CNN) program on care for patients with cleft lip and cleft palate and assess the programs efficacy to reduce existing socioeconomic disparities in care. Design: Retrospective review and outcomes analysis (n = 739). Setting: Academic tertiary care center. Patients: All patients presenting with cleft lip and/or cleft palate (CL/P) born between May 2009 and November 2019 with exclusions for atypical clefts, submucous cleft palates, international adoption, and very late presentation (after 250 days of life). Interventions: Multidisciplinary care coordination program facilitated by the CNN. Main Outcome Measures: Patient age at first outpatient appointment and age at surgery, reported feeding issues, weight gain, and patient-cleft team communications. Results: After CNN implementation, median age at outpatient appointment decreased from 20 to 16 days ( P = .021), volume of patient-cleft team communications increased from 1.5 to 2.8 ( P < .001), and frequency of reported feeding concerns decreased (50% to 35%; P < .001). In the pre-CNN cohort, nonwhite and publicly insured patients experienced delays in first outpatient appointment ( P < .001), cleft lip repair ( P < .011), and cleft palate repair ( P < .019) compared to white and privately insured patients, respectively. In the post-CNN cohort, there were no significant differences in first appointment timing by race nor surgical timing on the basis of racial identity nor insurance type. Conclusions: A variety of factors lead to delays in cleft care for marginalized patient populations. These findings suggest that a CNN can reduce disparities of access and communication and improve early feeding in at-risk cohorts.